2013
DOI: 10.1103/physrevlett.111.208101
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Collective Motion in Swarming Bacteria Undergoing Stress

Abstract: The collective motion of Bacillus subtilis in the presence of a photosensitizer is disrupted by reactive oxygen species when exposed to light of sufficient dosages and is partially recovered when light irradiation is suspended. The transition from a highly collective to a more random motion is modeled using an improved self-propelled model with alignment rule. The increment in noise level describes the enhanced uncertainty in the motion of swarming bacteria under stress as observed experimentally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(54 citation statements)
references
References 33 publications
4
50
0
Order By: Relevance
“…In general, the selective interactions introduced in this paper could make models of social agents more realistic. Furthermore, the proposed kinetic theory could be helpful for a closely related version of the Vicsek model, which was introduced by Lu et al [27] to describe their experiments on the collective motion of Bacillus subtilis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In general, the selective interactions introduced in this paper could make models of social agents more realistic. Furthermore, the proposed kinetic theory could be helpful for a closely related version of the Vicsek model, which was introduced by Lu et al [27] to describe their experiments on the collective motion of Bacillus subtilis.…”
Section: Discussionmentioning
confidence: 99%
“…3 one also sees perfect agreement with the three-mode analytical solution, Eq. (27), near the threshold.…”
Section: F a Numerical Methods For The Fredholm Equationmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon light illumination, the photodynamic action of protoporphyrin IX generated reactive oxygen species, which disrupted the function of flagellar motors and caused cells to become more tumbly, thus increasing the noise level. The authors measured the collective speed of cells during light illumination and demonstrated loss of collective motion due to increased noise level [95].The physicochemical environment of swarm cells can be controlled using microfluidic devices. Swiecicki et al used a microfluidic device to control the height of the liquid environment of E. coli swarm cells and recovered the key features of collective swarming dynamics, such as cluster formation [60].…”
mentioning
confidence: 99%